Measurement of the concentration of radon gas in the Toirano's caves (Liguria) - Bruzzone, Diego; Bussallino, Massimo; Castello, Gianrico; Maggiolo, Stefano; Rossi, Daniela (Annali di chimica, 2006)
The radioactive gas radon, intermediate term of the decay series of uranium and thorium, is the main contamination source of underground places and may be a risk for high concentration and long exposure time. European and Italian law requires radon concentration to be measured in workplaces and, if the "action level" of 500 Bq/m3 is reached, proper actions must be made in order to decrease the dose commitment. Considering natural showcaves or artificial cavities open to public, the exposition of the visitors is frequently small, due to the short residence time, but accompanying people, remaining underground for long time, may be subject to appreciable dose and the radon concentration should therefore be monitored. The high humidity in natural caves may impair the use of some measuring devices. Therefore, different detection methods were compared (ZnS scintillation counters, E-PERM electret ionisation chambers, cellulose nitrate alpha-track dosimeters) to select the best procedure for long-term investigation. The LR-115 (Kodak) alpha-track dosimeters were insensitive to humidity and permitted to monitor a great number of places at the same time. Measurements have been carried out in the speleological and archaeological site of the Toirano's Caves (Savona, Liguria, Italy) and several points were monitored for two years. Radon concentration strongly depends on the site and changes during the year, due to the difference between internal and external temperature. The maximum dose commitment during the visitors tour, considering the average yearly value of radon concentration, was found to be between 1.5 and 4 microSv. It was found that no risk exists for visitors, but the evaluation of the dose absorbed by the guides and their classification according to the radiation protection law requires a complete monitoring of the average yearly concentration of radon and of the total time spent by each worker into the cave.